EFEKTIVITAS PENERIMAAN PAJAK HOTEL DAN TEMPAT WISATA PADA PENDAPATAN ASLI DAERAH KABUPATEN MAROS - Masrullah Masrullah (Jurnal Riset Perpajakan: Amnesty, 2020)
This study aims to provide an overview of the effectiveness of ollecting local taxes on hotel taxes and tourist attractions in the 2013 maros regency financial institutions up to 2017. To achieve the purpose of this study, the research method used is qualitative field research or failed research with a descriptive approach that provides a clear picture of the problem of the problem under study, interpret and explain the data systematically obtained from the office of the regional finance agency in maros regency, which is conducting interviews with respondents containing sstatements. Based on the results of local tax collection it can be concluded that the level of effectiveness of hotel and tourist tax revenues in maros regency is not effective and is quite effective with achievement rates covering 100%. In hotel tax receipts ini 2013 to 2017 maros regency has been effective at 118,408% and tax revenue can be as early as 2013 to 2017 effective 72,00%.